Exploring Self-Regulated Learning: A Comparative Analysis of Activist and Non-Activist University Students - Jannah, Ghefira Raudhatul; Sari, Ratna (el-Tarbawi, 2023)
This research aims to analyse the levels of self-regulation in studying among activist and non-activist students, as well as the differences in self-regulation in studying between the two groups. The study was conducted among students of the Islamic Education Department at UMY batch 2019. The research employed a quantitative method, with data collection techniques utilizing questionnaires as primary data and interviews as secondary data. The research sample consisted of 110 students, selected through nonprobability purposive sampling. The interview respondents included 2 activist students, 2 non-activist students, 2 academic advisors, and 1 program secretary. The questionnaire data were analysed using descriptive statistical methods and independent sample t-tests. The interview data were analysed using the Miles, Huberman, and Saldana theory. The research findings indicate that self-regulation in studying among activist students is categorized as high, with an average score of 162, while self-regulation in studying among non-activist students is categorized as moderate, with an average score of 156. The significance of the t-value is 0.153, which is greater than 0.05.Therefore, the difference is consideredstatisticallyinsignificant,indicating no difference in self-regulation in studying betweenactivist and non-activist students. The findings from this article canprovide new ideas for developing educationalprograms that fosterself-regulation and support overall student development.